A New Method Based on Operational Strategies for Early Detection of Breast Cancers - Samira Khajehkhasan; Soheil Fakheri (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Breast cancer is one of the most important and common types of cancer in the world. There are two types of breast cancer: benign and malignant cancer. The benign condition has poor growth in the body and is rarely distributed in other areas of the body. It also has specific characteristics. However, in the malignant type, we see a tendency to spread faster, which is dangerous for a person's life. Therefore, its classification into these two modes is essential for diagnosis and treatment. Methodology: First, mammographic images of patients' breasts were evaluated with the help of doctors, and then the photos were processed. At this stage, we succeeded in using fuzzy logic to identify cancer and its type more quickly. Results: This article proposes a new algorithm for diagnosing benign and malignant cancers. Each benign and malignant branch has two types of tumor: adenosis and phyllodes tumor, and malignant has two types of duct and papillary cancer. This article proposes an algorithm for diagnosing breast cancer that includes four steps. The first stage is the preprocessing stage; the second stage is for image analysis, which uses wavelet transform to analyze images; the third stage is the extraction of valuable features that we use the results of wavelet transform to obtain; and the fourth stage That is, we use fuzzy logic to identify two types of benign or malignant images. Originality/Value: A new way to diagnose the disease and prevent it from becoming malignant is fundamental.